joom | júm, n. (Oxford English Dictionary, 2023)
Objectives To assess biomechanical properties of the ulnar nerve and flexor carpi ulnaris (FCU) muscle in young healthy adults using ultrasound shear wave elastography (SWE). Methods Using an elbow brace to standardize 30° and 90° of elbow flexion, shear wave velocity (SWV, m/s) of the ulnar nerve in cubital canal and FCU were measured using 18-MHz linear array transducer. The difference in SWV of ulnar nerve and FCU between both sides, between 30° and 90° elbow flexion, and between non-compression and compression conditions were analyzed using paired t-tests. Inter- and intra-observer reliability was analyzed using intraclass correlation coefficients (ICC) and Bland-Altman analysis. Results The study included 12 men and 12 women (mean age 26 ± 2 years) who had no upper extremity pathologies. No significant differences in nerve SWV were observed between male and female participants or between left and right sides (p > .05). Ulnar nerve SWV increased significantly under compression at 30° and 90° elbow flexion (p < .001) compared to non-compression. SWV of FCU also increased with muscle contraction at 30° and 90° elbow flexion compared to muscle relaxation (p < .001). A moderate and positive correlation in SWV between ulnar nerve and FCU was observed at variable elbow angles and stress conditions (Spearman r = 0.64, p < .001). Intra- and inter-observer reliability for performing SWE was moderate to good (ICC >0.79). Conclusions SWE is a feasible method for quantifying biomechanical properties of the ulnar nerve and FCU in young healthy adults under physiological conditions, demonstrating good inter- and intra-observer reliability and minimal measurement variability.